Pollinator preference and pollen viability mediated by flower color synergistically determine seed set in an Alpine annual herb. Issue 9 (22nd March 2017) - Mu, Junpeng; Yang, Yulian; Luo, Yanling; Su, Ruijun; Niklas, Karl J.
Abstract: Gentiana leucomelaena manifests dramatic flower color polymorphism, with both blue‐ and white‐flowered individuals (pollinated by flies and bees) both within a population and on an individual plant. Previous studies of this species have shown that pollinator preference and flower temperature change as a function of flower color throughout the flowering season. However, few if any studies have explored the effects of flower color on both pollen viability (mediated by anther temperature) and pollinator preference on reproductive success (seed set) in a population or on individual plants over the course of the entire flowering season. Based on prior observations, we hypothesized that flower color affects both pollen viability (as a function of anther temperature) and pollen deposition (as a function of pollinator preference) to synergistically determine reproductive success during the peak of the flowering season. This hypothesis was tested by field observations and hand pollination experiments in a Tibetan alpine meadow. Generalized linear model and path analyses showed that pollen viability was determined by flower color, flowering season, and anther temperature. Anther temperature correlated positively with pollen viability during the peak of the early flowering season, but negatively affected pollen viability during the peak of the mid‐ to late flowering season. Pollen deposition was determined by flower color, flowering season (early, or mid‐ to late season), and pollen viability. Pollen viability and pollen deposition were affected by flower color that in turn affected seed set across the peak of the flowering season (i.e., when the greatest number of flowers were being pollinated). Hand pollination experiments showed that pollen viability and pollen deposition directly influenced seed set. These data collectively indicate that the preference of pollinators for flower color and pollen viability changed during the flowering season in a manner that optimizes successful reproduction in G. leucomelaena . This study is one of a few that have simultaneously considered the effects of both pollen viability and pollen deposition on reproductive success in the same population and on individual plants. Abstract : Flower color polymorphism affects both pollen viability (as a function of anther temperature) and pollen deposition (as a function of pollinator preference) that synergistically determine reproductive success during the peak flowering season. This study is one of a few that have simultaneously considered the effects of both pollen viability and pollen deposition on reproductive success in the same population and on individual plants.